p2x+pqy-2pz-x=0
"\\frac{dp}{\\frac{df}{dx}+p\\frac{df}{dz}}=\\frac{dq}{\\frac{df}{dy}+q\\frac{df}{dz}}=\\frac{dz}{-p\\frac{df}{dp}-q\\frac{df}{dq}}=\\frac{dx}{-\\frac{df}{dp}}=\\frac{dy}{-\\frac{df}{dq}}"
"\\frac{dp}{p^2-1+p+-2p)}=\\frac{dq}{pq+q(-2p)}=\\frac{dz}{-p(2px+qy-2z)-qpy}=\\frac{dx}{-(2px+qy-2z)}=\\frac{dy}{-py}"
"\\frac{dp}{-p^2-1}=\\frac{dq}{-pq}=\\frac{dz}{-2p^2x-2pqy+2pz}=\\frac{dx}{-2px-qy+2z}=\\frac{dy}{-py}"
"\\frac{dp}{-p^2-1}=0"
-arctan(p)=a
p=tan(-a)=c
-pqdp=(-p2-1)dq
"\\frac{-p}{-p^2-1}dp=\\frac{dq}{q}"
Let t=p2, dt=2p
"\\int{\\frac{-p}{-p^2-1}dp}=-\\int{\\frac{1}{2(-t-1)}dt}=\\frac{1}{2}\\int{\\frac{1}{t+1}dp}=\\frac{ln(t+1)}{2}=\\frac{ln(p^2+1)}{2}"
"\\frac{ln(p^2+1)}{2}=lnq"
p2+1=q2
"q=\\sqrt{p^2+1}=\\sqrt{c^2+1}"
dz=pdx+qdy
"dz=cdx+\\sqrt{c^2+1}dy"
"z=cx+\\sqrt{c^2+1}y+b"
y=1, x=z
"z=cz+\\sqrt{c^2+1}+b"
"z(1-c)=\\sqrt{c^2+1}+b"
"z=\\frac{\\sqrt{c^2+1}+b}{1-c}"
Answer:"c^2x+c\\sqrt{c^2+1}y=2cz+x"
Comments
Using that differential equation one can conclude p is constant. It can be proved because pdp/(p^2+1)=dq/q=dy/y. If the function of p simultaneously depends on different variables, it is constant.
How you have taken dp/(p^2)-1=0 give reason
Leave a comment